Case Report: Rare multisystem metastasis in head and neck paraganglioma with SDHB pathogenic variant and KIF1B VUS manifested as FUO - Yang, Yongshi; Tian, Xiaotong; Jia, Congwei; Fan, Hongwei; Li, Taisheng; Zhang, Li; Liu, Zhengyin (Frontiers in Endocrinology, 2025)
BackgroundParagangliomas (PGLs) are rare neuroendocrine tumors originating from the extra-adrenal autonomic paraganglia with a strong genetic background. SDHB pathogenic variants are associated with the highest rate of malignancy in PGLs. Most head and neck paragangliomas (HNPGs) are asymptomatic and benign, and multiple metastases are rare.Case presentationA 37-year-old man presented at our hospital with a fever of unknown origin (FUO) without any other complaints except for mild consumption lasting over 6 months. Laboratory examinations showed elevated inflammatory markers (CRP, ESR, IL-6, and Ferritin) but no abnormalities in infection, immune, or tumor markers. Imaging examination found an oval-shaped space-occupying lesion in the right parapharyngeal space, with rare and unique vertebral imaging findings. Octreotide imaging and 68Ga-FAPI PET/CT scans indicated a potential for neuroendocrine tumors with lymph nodes, bone, and lung metastases. Pathology demonstrated metastatic paraganglioma. Whole-genome sequencing identified an SDHB pathogenic variant and a KIF1B variant of uncertain significance. Following multidisciplinary consultation, the patient opted for the cyclophosphamide-vincristine-dacarbazine (CVD) chemotherapy regimen and was subsequently transferred to a regional hospital for coordinated follow-up.ConclusionsThis case reported rare co-occurring variants in SDHB and KIF1B and unusual imaging findings of metastasis in paraganglioma. A multimodal imaging evaluation and whole-genome sequencing were instrumental in assessing paraganglioma patients. This case suggested that atypical imaging features should raise suspicion of malignant diseases and underscored the importance of interdisciplinary collaboration in guiding the diagnosis and treatment of complex and rare clinical cases.